Assessment Challenges Encountered by Teachers in the Implementation of Printed Modular Distance Learning - Arzaga, Jaybie S. (Future Science / FSH-PH Publications, 2023)
The COVID-19 pandemic brought about unprecedented challenges in the field of education. Printed Modular Distance Learning (PMDL) was one of the most challenging modes of instruction in basic education, and the assessment stage posed specific difficulties for secondary school teachers in the Schools Division of Puerto Princesa City during the School Year 2020-2021. This research aimed to explore the real-life experiences of 15 secondary school teachers who taught via PMDL. Using a phenomenological study, the researcher conducted individual interviews with the teachers, who were chosen through purposive sampling. The study found that teachers encountered various challenges during the implementation of PMDL, with specific difficulties arising during the assessment stage. One of the significant problems reported by the participants was the submission of unanswered or incomplete modules by some students. Additionally, some learners had modules that were answered by their parents or other family members, while others copied answers directly from the internet or answer keys. The lack of names on modules and illegible handwriting also added to the challenges experienced by the teachers. Furthermore, the sheer volume of modules to be checked was a significant challenge for the participants. To ensure the quality and validity of module-based assessments, it is recommended that guidelines be provided to learners, monitoring and feedback mechanisms be put in place, and policies that prevent cheating be implemented. Educators should also have workload management strategies to ensure timely grading and feedback.